Dynamics and conformational stability of chiral bay-phenolate-substituted twisted octaazaperopyrenedioxides (OAPPDOs) - Rojas Deij, Bastian; Schneider, Lars; Bruckhoff, Tim; Eichelmann, Robert; Rohrmann, Philipp; Candalh, Raphael; Ballmann, Joachim; Deschler, Felix; Gade, Lutz H. (Chemistry - a European journal, 2025)
Configurationally stable chiral octaazaperopyrene dioxide (OAPPDO) derivatives were obtained by nucleophilic substitution of chiral BINOL and related fragments as bridging units onto the bay position. The addition of these phenolate derivatives has given rise to a new group of bright chiral fluorophores with remarkable thermal stability, which allowed the study of their chiroptical properties, in particular, their circular dichroism characteristics as well as circular polarized luminescence (CPL), albeit with a low dissymmetry factor (glum) in the range of 2*10−4. The introduction of the BINOL bridging groups in the bay position led to equilibria between chiral conformers in solution, the interconversion of which has been studied by DFT modeling, with the two lowest energy species being directly observable in situ by NMR. Insight into the stability of these derivatives with respect to overall racemization has been obtained by DFT modeling which established an overall activation barrier for the process of above 170 kJ mol−1.